2017
DOI: 10.1038/hdy.2016.123
|View full text |Cite
|
Sign up to set email alerts
|

No signs of inbreeding despite long-term isolation and habitat fragmentation in the critically endangered Montseny brook newt (Calotriton arnoldi)

Abstract: Endemic species with restricted geographic ranges potentially suffer the highest risk of extinction. If these species are further fragmented into genetically isolated subpopulations, the risk of extinction is elevated. Habitat fragmentation is generally considered to have negative effects on species survival, despite some evidence for neutral or even positive effects. Typically, non-negative effects are ignored by conservation biology. The Montseny brook newt (Calotriton arnoldi) has one of the smallest distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 80 publications
4
33
3
Order By: Relevance
“…Similar surprising findings, i.e. high allelic richness, high genetic diversity and a very low inbreeding coefficient, were also observed in the Black toad and the Montseny brook newt 39 , 40 . This demonstrates that species with small N ad and N e are not necessarily genetically depauperate.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Similar surprising findings, i.e. high allelic richness, high genetic diversity and a very low inbreeding coefficient, were also observed in the Black toad and the Montseny brook newt 39 , 40 . This demonstrates that species with small N ad and N e are not necessarily genetically depauperate.…”
Section: Discussionsupporting
confidence: 75%
“…When we compared our results to those of two other studies focusing on similar systems, i.e. geographically very restricted amphibian species without viable metapopulation structures, we found that comparatively low N e values had also been reported (i) for the Black toad ( Anaxyrus exsul , formerly Bufo exsul ), a desert amphibian inhabiting four spring systems with a total range of only ~15 ha in California, for which N e values ranged between 7 and 30 39 , and (ii) for the Montseny brook newt ( Calotriton arnoldi ), one of the most endangered European vertebrate species with an overall distribution range of only 8 km², for which N e values ranged between 7.3 and 342.3 40 . These two species, however, already diverged from their sister species during the Pleistocene glaciations 39 41 and successfully persisted until today despite their isolation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…asper populations across the Pyrenees (weighted average Ar = 2.930 and H E = 0.523) compared to its sister species, the Montseny brook newt, C . arnoldi (weighted average Ar = 3.398 and H E = 0.441)[ 26 ]. These values are also consistent compared to other mountain brook newts, such as Euproctus platycephalus on Sardinia (weighted average Ar = 2.376 and H E = 0.6 [ 65 ]) and are within the typical range of other urodeles and temperate amphibians (0.4–0.6; [ 66 ] and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, highly phylopatric amphibian species with very restricted dispersal rates (e.g. Calotriton arnoldi ) present highly structured and isolated populations [ 26 ].…”
Section: Introductionmentioning
confidence: 99%